Opportunistic viral infections in intestinal transplantation. Issue 4 (April 2013) - Florescu, Diana F; Langnas, Alan N; Sandkovsky, Uriel
Intestinal transplantation (IT) has become a standard treatment for patients with intestinal failure and complications of parenteral nutrition. The pool of intestinal transplant recipients has been slowly growing over the last two decades. Of the 2191 ITs performed between 1 January 1990 and 31 March 2012, 50.5% were children less than 10 years of age. Survival rates at 1, 5 and 10 years have been reported to be 78.5, 58.2 and 47%, respectively. IT restores organ functions, but it is associated with complications, with infections representing the major cause of morbidity and mortality in this population.